2015
DOI: 10.1103/physrevd.91.085006
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement entropy between real and virtual particles inϕ4quantum field theory

Abstract: The aim of this work is to compute the entanglement entropy of real and virtual particles by rewriting the generating functional of ϕ 4 theory as a mean value between states and observables defined through the correlation functions. Then the von Neumann definition of entropy can be applied to these quantum states and in particular, for the partial traces taken over the internal or external degrees of freedom. This procedure can be done for each order in the perturbation expansion showing that the entanglement … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is well known that the vacuum state of a quantum field is highly entangled, which implies that regions that are spacelike separated contain correlations for those observables that depends on the field [1][2][3]. This physical fact has many consequences in different branches of quantum field theory [4][5][6][7][8][9]. In addition, it has been shown that two detectors that remain spacelike separated can interact locally with the vacuum state getting entangled and the harvested correlations approximation to the light-matter interaction when no angular momentum is transferred [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the vacuum state of a quantum field is highly entangled, which implies that regions that are spacelike separated contain correlations for those observables that depends on the field [1][2][3]. This physical fact has many consequences in different branches of quantum field theory [4][5][6][7][8][9]. In addition, it has been shown that two detectors that remain spacelike separated can interact locally with the vacuum state getting entangled and the harvested correlations approximation to the light-matter interaction when no angular momentum is transferred [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The vacuum state of a free quantum field, contains correlations of different observables in separate region of spacetime, even when those regions are spacelike separated ( [1], [2], [3]). This nonclassical behavior of the vacuum state of the field is a vital concept in phenomena such as quantum collect calling [4], the black hole information loss problem ( [5], [6]) and quantum energy teleportation ( [7], [8] and [9]). These correlations are, in principle, physically accessible because they can be obtained from the field vacuum via quantum particles detectors that couple to it locally ( [10]).…”
Section: Introductionmentioning
confidence: 99%